Management of platinum-sensitive relapsed ovarian cancer, with particular reference to the International Collaboration in Ovarian Neoplasm-4/Arbeitsgemeinschaft Gynakologische Onkologie Ovarian Cancer-2.2 trial. (1st April 2005) - Kaye, S. B.
Abstract : Substantial progress has been made since the early 1990s regarding the treatment of patients with ovarian cancer. Those patients relapsing more than 6 months after platinum-based chemotherapy may benefit from repeat chemotherapy that includes carboplatin. When the treatment-free interval is >12 months, carboplatin combined with paclitaxel (or possibly another agent) is likely to provide a survival advantage compared with carboplatin monotherapy. Evidence to support this comes from the International Collaboration in Ovarian Neoplasm-4/Arbeitsgemeinschaft Gynakologische Onkologie Ovarian Cancer-2.2 trial, a prospective randomized trial of 802 patients designed to assess the potential benefit of combining carboplatin with paclitaxel. One arm of the trial contained patients randomized to conventional platinum-based therapy, while those randomized to the second arm received a paclitaxel–platinum combination. There was a 7% increase in survival for paclitaxel-based treatment (2-year increase from 50% to 57%; P = 0.02) and a 10% increase in progression-free survival (1-year increase from 40% to 50% in favor of paclitaxel-based treatment; P = 0.0004). The major observed differences between the treatment arms in terms of toxicity were significant alopecia (25% versus 86% in arms 1 and 2, respectively), neurotoxicity (1% versus 20%), and hematologic toxicity (46% versus 29%). When the treatment-free interval was between 6 and 12 months, the extent of the benefit was less clear and further trials are certainly warranted.